Begging and ectoparasite attraction - Tomás Gutierrez, G. (2016)
Honesty of offspring begging behaviours is the keystone to understanding the evolution of parent-offspring communication. Three main begging costs have been traditionally advocated that ensure the reliability of offspring signalling: energy expenditure, loss of inclusive fitness and attraction of predators. Here, we propose that ectoparasites may eavesdrop on begging signals, especially acoustic signals, for host detection, a never considered but potentially generalized cost of begging that will constrain the evolution of exaggerated begging displays. Ectoparasitic insects possess a diversity of auditory systems for intraspecific communication that may be used to detect begging calls of host offspring. The use of auditory cues for host detection offers some advantages to ectoparasites, particularly in environments in which long-distance detection of hosts is necessary. There are well-known examples of interspecific eavesdropping on host auditory signals by parasites that include parasitoid flies attracted to calling crickets and cicadas, and frog-biting midges and mosquitoes attracted to frog calls. Eavesdropping on begging signals may have evolved in those parasites searching for hosts that display begging behaviours, which include not only birds but also mammals and some reptiles and insects with parental care of juveniles. Considering begging costs due to detection by ectoparasites may help us understand the reliability, and therefore the evolution, of signals of need and parent-offspring communication. © 2016 The Association for the Study of Animal Behaviour.